KAJIAN PSIKOLINGUISTIK TERHADAP BENTUK DAN FUNGSI LINGUAL LATAH: STUDI KASUS WARGA MEDAN - Andi Saputra Tanjung; Gustianingsih Gustianingsih; Syahron Lubis (Balai Bahasa Sumatera Utara, 2019)
hyperstartle syndrome is interesting to research using psycholinguistic study. This research electorates the linguistic form of language of the residents in Jalan Garu III, Medan Amplas, Kota Medan. The qualitative data are words and sentences that used in behavior in Jalan Garu III, Medan Amplas, Kota Medan. The result of the research is the description of the linguistic forms of talkative behavior in the form of words and sentences, including: (1) coprolalia talkative behavior, (2) ecolalia talkative behavior, (3) autoecolalia talkative behavior, (4) automatic obedience talkative behavior. This research discovers some language functions: (1) self expression, (2) interactional function, and (3) personal function.